2021
DOI: 10.3390/polym13132208
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-Modified Chitosan Poly(lactic-co-glycolic acid) Microspheres Act as a Mannose Receptor-Mediated Delivery System Enhancing the Immune Response

Abstract: The mannose receptor (MAN-R)-targeted delivery system is commonly used to deliver antigens to macrophages or immature dendritic cells (DCs) to promote the efficiency of antigen presentation. To maximize the enhancement effects of chitosan (CS) and induce an efficient humoral and cellular immune response against an antigen, we encapsulated ovalbumin (OVA) in poly(lactic-co-glycolic acid) (PLGA) microspheres (MPs) and conjugated it with MAN-modified CS to obtain MAN-R-targeting nano-MPs (MAN-CS-OVA-PLGA-MPs). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…The in vivo immune response of the MPs was investigated using a mouse model. The results demonstrated that MAN-CS-OVA-PLGA-MPs significantly increased OVA-specific IgG and IgG isotope antibody levels, suggesting that mannose modification significantly enhanced the humoral immune response of CS-OVA-PLGA-MPs ( 36 ). In the present study, the REV-specific IgG antibody titers in the immunized chicks in the CS-gp90@M treated group were significantly increased compared to chicks in the CS-gp90 treatment group, suggesting that erythrocyte membrane coating could promote humoral responses induced by CS-gp90.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo immune response of the MPs was investigated using a mouse model. The results demonstrated that MAN-CS-OVA-PLGA-MPs significantly increased OVA-specific IgG and IgG isotope antibody levels, suggesting that mannose modification significantly enhanced the humoral immune response of CS-OVA-PLGA-MPs ( 36 ). In the present study, the REV-specific IgG antibody titers in the immunized chicks in the CS-gp90@M treated group were significantly increased compared to chicks in the CS-gp90 treatment group, suggesting that erythrocyte membrane coating could promote humoral responses induced by CS-gp90.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrastructure of the sample was observed using TEM (Tecnai G2 F20 S‐TWIN, FEI, Hillsboro, Oregon, USA), and images were obtained. Each sample was observed and imaged three times 29 …”
Section: Methodsmentioning
confidence: 99%
“…The sample table was placed on an ion sputtering instrument, coated with a layer of conductive gold powder, and was placed under the SEM system (JEOL, JSM-7500F, Tokyo, Japan) and observed. Each sample was photographed three times to eliminate sample interference and system errors [ 34 ].…”
Section: Methodsmentioning
confidence: 99%